The Photoluminescence and Ferromagnetic Behavior of Sprayed LaMnO2.75 thin Layers - Arrar, A.; Benhaliliba, M.; Boukhachem, A.; Ayeshamariam, A. (Algerian Journal of Research and Technology (AJRT), 2020)
The study of Sr-doped lanthanum manganites (La1-xSrxMnO2.75, LSMO) with x= 0 and 0.4 are synthesized by spray pyrolysis method onto glass substrate at 460°C. The structural properties of the prepared samples are characterized by X-ray diffraction (XRD) technique and some parameters such as lattice parameters, crystallite size, microstrain and dislocation density have been reported. It is shown that LaMnO2.75: Sr thin films crystallize in orthorhombic structure with a preferred orientation of the crystallites along (040) direction. In addition, atomic force microscopy (AFM) investigation displays the nanosphere aspect. UV-VIS-IR measurements show that the average transmittance of the LaMnO2.75: Sr thin films is greater than 70% and optical band gap (Eg) of 2.85 eV is recoded. The photoluminescence (PL) measurements exhibit emission in the visible region, which is located at 530 nm. Finally, magnetic measurements at room temperature using vibrating sample magnetometer (VSM) technique reveal ferromagnetic behavior.